Lousy and Lovely Jobs: The Rising Polarization of Work in Britain - Goos, Maarten; Manning, Alan (The Review of Economics and Statistics, 2007)
This paper shows that the United Kingdom since 1975 has exhibited a pattern of job polarization with rises in employment shares in the highest- and lowest-wage occupations. This is not entirely consistent with the idea of skill-biased technical change as a hypothesis about the impact of technology on the labor market. We argue that the “routinization” hypothesis recently proposed by Autor, Levy, and Murnane (2003) is a better explanation of job polarization, though other factors may also be important. We show that job polarization can explain one-third of the rise in the log(50/10) wage differential and one-half of the rise in the log(90/50).